Comparative effect of artemether-lumefantrine and artesunate-amodiaquine on gametocyte clearance in children with uncomplicated Plasmodium falciparum malaria in Madagascar - Malalanandrianina A. Rakotoarisoa; Jocia Fenomanana; Bronislaw Tchesterico Dodoson; Voahangy Hanitriniaina I. Andrianaranjaka; Arsène Ratsimbasoa (figshare, 2022)
Abstract Background Gametocytes are the sexual stages ensuring continuity of the development cycle of the parasite, as well as its transmission to humans. The efficacy of artemisinin-based anti-malarials against asexual stages of Plasmodium has been reported in Madagascar, but their effects on gametocytes are not well documented. The present study aims to determine the emergence of gametocyte and gametocyte clearance after artesunate-amodiaquine (ASAQ) or artemether-lumefantrine (AL) treatment in children with uncomplicated Plasmodium falciparum malaria in 5 regions of Madagascar. Methods 558 children with uncomplicated P. falciparum malaria, aged between 1 and 15 years, were assigned randomly to AL or ASAQ treatment. They come from 5 regions of Madagascar with different epidemiological facies related to malaria: Ankilivalo, Benenitra, Ampanihy, Ankazomborona and Matanga. Gametocytes were identified by microscopy, from t blood smears at day 1, day 2, day 3, day 7, day 14, day 21 and day 28 after treatment. Results At baseline, 9.7% (54/558) children [95% CI: 7.4–12.5%] had detectable gametocyte by microscopy. Among the 54 enrolled children, gametocytes emergence rate was high during the first days of treatment in both treatment arms (AL and ASAQ), especially on day 1. Gametocytes were undetectable from day 14 for AL arm while for ASAQ arm, gametocyte carriage was gradually decreased but persisted until day 21. Conclusion This study demonstrates that AL has a more rapid effect on gametocyte clearance compared to ASAQ in children with uncomplicated Plasmodium falciparum malaria.
Keywords: 29999 Physical Sciences not elsewhere classified; Medicine; Cell Biology; Cancer; 110309 Infectious Diseases; 60506 Virology; Computational Biology